Objektivikasi Subjek dalam Budaya Kontemporer berdasarkan Konsep Hiperrealitas Jean Baudrillard - Masut, Vinsensius Rixnaldi; Wijanarko, Robertus; Pandor, Pius (Jurnal Filsafat Indonesia, 2023)
This study aims to explain Jean Baudrillard's concept of hyperreality specifically the objectification of the subject in the context of contemporary culture. According to Jean Baudrillard, in the world of hyperreality which is controlled by the latest information and communication technology, humans have lost their subjectivity. The object has controlled the subject so that there is no other choice for the subject but to allow himself to be in the control of the object. The objectification character of this subject is evident in the subject's passivity when using the internet, being in front of the television, and also the advertising machine. According to Baudrillard, in the face of these three forms of contemporary culture, the subject has been reduced to an object so that the subjectivity and dimensions of the subject's consciousness become dead. The methodology used in this study is a qualitative method by conducting a literature study. The author specifically explores Jean Baudrillard's writings entitled “Simulacra and Simulation” (1981) which discusses a lot about the concept of hyperreality. The findings of this study are (1) subjects in contemporary culture have been reduced to objects through the simulation and simulacra skills of mass media technology, especially the internet, television, and advertising; (2) the objectification of this subject can be countered by re-realizing human subjectivity, namely the subject of consciousness.